The Influence of Information System Quality, Facilities, and Competence on Inpatient Satisfaction With Service Quality as an Intervening Variable at Raja Ahmad Thabib Hospital, Riau Islands Province - Ira Wardeni; Bambang Satriawan; Muammar Khaddafi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study examines the impact of information systems, facilities, and competence on inpatient satisfaction with service quality as an intervening variable at Raja Ahmad Thabib Hospital, Riau Islands Province. The sample for this study consists of 100 individuals who either received healthcare services or are family members of patients. The research method employed is an associative method with a quantitative approach, utilizing Partial Least Square (PLS) analysis techniques through the SmartPLS Version 4.0 program. The results of the study indicate that the information system has a positive and significant effect on the satisfaction variable, facilities have a positive and significant effect on the satisfaction variable, competence does not significantly affect the satisfaction variable, service quality significantly affects the satisfaction variable, competence does not significantly affect the service quality variable, the information system has a positive and significant effect on the service quality variable, facilities have a positive and significant effect on the service quality variable, the information system positively and significantly affects the satisfaction variable with service quality as an intervening variable, facilities positively and significantly affect the satisfaction variable with service quality as an intervening variable, and competence does not significantly affect the satisfaction variable with service quality as an intervening variable at Raja Ahmad Thabib Hospital, Riau Islands Province.